Tinjauan Yuridis Pengisian Jabatan Wakil Bupati Berdasarkan Undang Nomor 10 tahun 2016 tentang Perubahan Kedua Undang-Undang nomor 1 tahun 2015 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang nomor 1 tahun 2014 tentang Pemilihan Gubernur, Bupati, Walikota - Andi Wahyu Putra Utama; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The 1945 Constitution of the Republic of Indonesia in Article 18 paragraph 4 which isthat the Governor, Regent and Mayor are democratically elected to function to lead their regionswhich have been given the trust of the people who have given their votes in the regional headelection. However, problems related to Regional Autonomy seem never to be resolved. Theproblem that has arisen in the relationship between the central and regional governments is thedistribution of power and the allocation of financial resources. The exsistence of a deputy regentin principle aims to help ease the tasks of the regional head. The representative should be a“trusted person” or right-hand man of the regional head who has an emotional attachment toone another. This trust will be a obtained if a regional head can freely choose his representativewithout being bound to a system or management that is coercive.This type of research can be classified in the type of Normative legal research, whichreveals legislation relating to legal theories that are the object of research. The approach takenuses a qualitative analysis approach by looking for data both in books, journals and otherscientific works related to this research. The data sources used are primary and secondary legalmaterials.The conclusion that can be obtained from the results of the research is first, the filling ofthe position of Deputy Regent has been regulated based on law number 10 of 2016 after thesecond amendment to Law number 1 of 2015 concerning the Establishment of GovernmentRegulation in lieu of Law number 1 of 2014 concerning Governor Election Regent and Mayorrelated to the vacant position of deputy regent, it is stated in law number 10 of 2016 article 176.Second, the ideal arrangement for filling the position of Deputy Regent in the Constitutionmandates in Article 18 Parageraph 4 oh the 1945 Constitution thet “Governor, The Regent, andthe Mayor respectively as the heads of the provincial, regency and city regional governments aredemocratically elected. “An important issue that arises is related to the existence and urgency ofthe position of Deputy Governor, Deputy Regent, or Deputy Mayor. Explicitly, the constitutiononly recognizes the positions of Governor, Regent and Mayor.Keywords: Position, Deputy Regent, Election, Filling, Regional Autonomy.